A Study on the Three-Dimensional Optimization Paths to Improve Primary and Secondary School Teachers’ Acceptance of Digital Textbooks - Hou, Mengjun (Journal of Educational Research and Policies, 2025)
This study, grounded in the Technology Acceptance Model and structured interviews, reveals that primary and secondary school teachers’ acceptance of digital textbooks is influenced by the intricate interplay of individual psychological capital, technology-teaching fit, and the organizational support system. To boost teachers’ acceptance, a three - dimensional optimization framework is proposed. This framework encompasses cognitive reconstruction, scenario adaptation, and ecological construction. Cognitive reconstruction enhances teachers’ internal motivation for technology adoption through dynamic adjustment of their cognitive structures. Scenario adaptation optimizes the functional compatibility of digital textbooks based on the unique features of teaching contexts. Ecological construction, via the organizational support system, establishes an institutional guarantee for sustainable development. Additionally, strategies such as hierarchical teacher training, school - level technical emergency mechanisms, subject - specific tool module development, teaching process scaffolding, interdisciplinary mentorship, and dynamic demand feedback loops are elaborated to implement this optimization path, aiming to facilitate the effective integration of digital textbooks in teaching.